Venous malformation arising in the pterygomandibular space: A case report. Issue 2 (March 2019) - Ito, Yu; Abe, Atsushi; Adachi, Moriyasu
Abstract: We report a rare case of venous malformation in the pterygomandibular space. A 49-year-old Japanese woman experienced discomfort on opening her mouth since 3 months but had not sought treatment previously. At initial examination, no submandibular lymph node enlargement, trismus, perceptual dysfunction were noted. The surface mucosa on the lateral wall of the left middle pharynx was normal, and no mass could be palpated in the oral cavity. Panoramic X-ray examination revealed a clearly demarcated, elliptical, radiolucent area on the left mandibular ramus. Computed tomography revealed a clearly demarcated, nearly spherical mass of 17 × 11 × 16 mm near the mandibular foramen of the left mandibular ramus. Magnetic resonance imaging revealed signal hypointensity, which was approximately similar to that of muscle tissues, on T1-weighted images and signal hyperintensity on T2-weighted images. On contrast T1-weighted images, a mass with relatively good contrast effects and some internal areas of low concentration was revealed. A clinical diagnosis of benign tumor in the left pterygomandibular space was made, and enucleation was performed using intraoral approach under general anesthesia. The tumor was dark purple and encapsulated. It showed color-fading and was not pulsatile. Although venous vascular malformation was suspected, en bloc extraction including the capsule could be performed because no adhesion with surrounding tissue or blood vessels was observed. Histopathological diagnosis was venous malformation. Although neurological deficit symptoms in the lower lip and tongue were observed postoperatively, subsequent improvement was noted. Currently, at >5 postoperative years, no recurrence has been found.